Trust rhetoric and CEO gender - Wolfgang Breuer; Andreas Knetsch; Astrid Juliane Salzmann (Review of Financial Economics, 2023)
This study investigates the perceived and actual trustworthiness of female managers when using rhetoric to advertise their trustworthiness in public disclosure documents. We find that the stock market reacts more favorably to trust rhetoric if the document has been prepared under the responsibility of a female CEO rather than a male CEO. We rule out that this result could be driven by female and male CEOs talking about trust in different contexts. However, inconsistently with the notion that the trust rhetoric of women managers is more truthful than that of their male counterparts, trust rhetoric does not relate to less extensive earnings manipulation if such rhetoric stems from female CEOs compared to male CEOs. Our results thus do not confirm the popular view that higher female trustworthiness explains gender differences in accounting behavior.
Keywords: 330; earnings management; female CEOs; stock market reactions; textual analysis; trust